2013
DOI: 10.1073/pnas.1214741110
|View full text |Cite
|
Sign up to set email alerts
|

Rate of hydrolysis in ATP synthase is fine-tuned by α-subunit motif controlling active site conformation

Abstract: Computer-designed artificial enzymes will require precise understanding of how conformation of active sites may control barrier heights of key transition states, including dependence on structure and dynamics at larger molecular scale. F o F 1 ATP synthase is interesting as a model system: a delicate molecular machine synthesizing or hydrolyzing ATP using a rotary motor. Isolated F 1 performs hydrolysis with a rate very sensitive to ATP concentration. Experimental and theoretical results show that, at low ATP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…2013 ). The conformational dependence of the catalytic step has been explored recently by Beke-Somfai et al . (2013) , who used QM/MM calculations and phenomenological description to model the process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2013 ). The conformational dependence of the catalytic step has been explored recently by Beke-Somfai et al . (2013) , who used QM/MM calculations and phenomenological description to model the process.…”
Section: Discussionmentioning
confidence: 99%
“…The conformational dependence of the catalytic step has been explored recently by Beke-Somfai et al . (2013), who used QM/MM calculations and phenomenological description to model the process. It was concluded that the activation barrier is reduced significantly upon T to D change of the active site.…”
Section: Discussionmentioning
confidence: 99%
“…These simulations also allow us to explore the coupling between the 40°s ubstep and P i release, and to examine the underlying molecular mechanisms. F 1 has been studied by molecular simulations at various levels of resolution, including quantum chemical calculations of ATP hydrolysis (25)(26)(27), all-atom simulations of conformational changes in the β-subunit (28,29), of ATP release (30), of fluctuations in the complex (31,32), and of γ-rotation (33,34), as well as coarse-grained simulations of γ-rotation (35)(36)(37). As in experiment and in earlier simulations (33), we apply external torque to modulate the rates of the functional processes, including P i release.…”
mentioning
confidence: 99%
“…17,18 Here the O W ···γP distance is 2.10 Å, while the γP···O(-βP) distance is 2.71 Å, which is somewhat longer than those of observed for the other enzymes.…”
mentioning
confidence: 72%